The Complex Reality and Trans-disciplinary Approach in World of Higher Education - Lubis, Akhyar Yusuf (Golden Ratio of Social Science and Education, 2024)
This paper discusses the transdisciplinary approach and its importance to be discussed and applied in the world of higher education research to understand and address the complexity of socio-cultural problems. Gillez Deleuze and Felix Guattari through a famous book, A Thousand Plateaus proposed two terms "arborescent" and "rhizome" as a metaphor for two paradigms and scientific approach in teaching and research. The concept “aborrescent” in many respects considered inadequate applied in the scientific world that tends to see reality is atomistic, but complex and mutually overlap (networking). Giles Deleuze and Felix Guattari proposed the concept of the rhizome as a metaphor for the paradigm and post-disciplinary scientific approach. UNESCO, CIRET and many scientific institutions and university in developed countries have done symposium, seminars and carry out research with a trans-disciplinary approach. The development of science-technology and complex and fast-changing cultural reality, requires colleges to understand and apply the trans-disciplinary approach.